Atypical Hemolytic Uremic Syndrome with Severe Extrarenal Manifestations: a Case Report - Kosan, Celalettin; Kucuk, Nuran (Journal of Pediatric Nephrology, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Atypical hemolytic uremic syndrome (aHUS) is a rare and life-threatening disease that may lead to end-stage renal failure (ESRF) or death, and may be accompanied by a variety of extrarenal manifestations. We presented a child with aHUS accompanied by severe extrarenal manifestations. A 12-year-old girl was visited in the emergency departments with acute renal failure, symptoms of fluid overload, vomiting, and somnolence. Laboratory tests revealed microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure with severe electrolyte imbalance. Diagnosis of HUS was made and emergency hemodialysis was performed to decrease the circulating volume, restore the electrolyte disturbance, and support the treatment of HUS, but conventional medical therapies were ineffective. The patient experienced frequent seizures and multiple cardiac arrests and became comatose. Thereafter, although she was diagnosed with aHUS, plasma infusions and plasmapheresis were performed. Upper gastrointestinal endoscopy and colonoscopy revealed erosive pangastritis, widespread gastric hemorrhagic ulcers, bulbitis, and hemorrhagic colitis. Since there was no improvement, the patient was transferred to a central university hospital where eculizumab was started. She responded to eculizumab. In conclusion, as aHUS can progress rapidly and is frequently fatal if untreated, it is important to be aware of unusual presentations and diagnose the condition promptly, particularly if supportive treatment is of little or no help.